Allelic polymorphism of Ovar-DRB1 exon2 gene and parasite resistance in two dairy sheep breeds (International Journal of Health, Animal Science and Food Safety, 2016)
The Ovar-DRB1 gene locus is one of the most polymorphic genes of the Major Histocompatibility Complex (Ovar-MHC) and holds a functional role to antigen presentation. The aim of this study was: a) to describe the Ovar-DRB1 locus variability in two dairy Greek sheep breeds and b) to investigate associations between this variability with resistance to gastrointestinal parasitosis. Blood and faecal samples were collected from 231 and 201 animals of Arta and Kalarrytiko breeds, respectively. The identification of alleles was performed using the sequence–base method. Faecal egg counting (FEC) of the gastrointestinal parasites and measures of blood plasma pepsinogen levels were performed in order to evaluate parasitological parameters. From this study in the overall examined animals, thirty-nine Ovar-DRB1 alleles were identified, among them, ten new alleles, reported for the first time in the literature. In Arta breed a total of twenty-four alleles were found. Among the detected alleles, ten were breed specific and five were new. Regarding the Kalarrytiko breed, twenty-nine alleles were found, fifteen of them were unique and nine were new. The studied breeds differed in their allelic profile, with only 12 common from the total of 134 different recorded genotypes. A higher number of animals with high parasitic load and high plasma pepsinogen values were found in Kalarrytiko. Associations between Ovar-DRB1 alleles with FEC values were found with certain heterozygous genotypes to present significantly reduced FEC values. The large number of detected alleles with low frequencies and the fact that the majority of animals were heterozygous, make hard to find strong associations
Keywords: dairy sheep; Greek breeds; Ovar-DRB1 exon2 alleles; genetic polymorphism; parasites.